Psammomatous ossifying fibroma of frontal sinus: a case report with review of literature - Sarkar, Rema Nair; Vasundhara, M.; Lakshmi, A. Bhagya; Ramadas, R. (International Journal of Research in Medical Sciences, 2017)
Psammomatoid Ossifying Fibroma (POF) is a rare, slowly progressive benign tumor of the extragnathic craniofacial bones representing a subgroup of related fibro-osseous lesions with a tendency towards locally aggressive behaviour unique to the nasal cavity, paranasal sinuses, orbit and is often misdiagnosed. Histologically they are benign, but clinically they are locally aggressive. We report a case of a 17 year-old boy who presented with psammamatous ossifying fibroma of the frontal sinus. The location of this tumor made this case unusual.